Long intergenic noncoding RNA 299 methylation in peripheral blood is a biomarker for triple-negative breast cancer. (13th September 2018) - Bermejo, Justo L; Huang, Guanmengqian; Manoochehri, Mehdi; Mesa, Karen G; Schick, Matthias; Silos, Rosa G; Ko, Yon-Dschun; Brüning, Thomas; Brauch, Hiltrud; Lo, Wing-Yee; Hoheisel, Jörg D; Hamann, Ute
Aim: To identify DNA methylation biomarkers in peripheral blood samples from triple-negative breast cancer (TNBC) patients.Materials & methods: We conducted an epigenome-wide association study (EWAS): the most promising markers were identified in 233 TNBC case–control pairs (discovery set) and subsequently validated in an independent validation set (57 TNBC patients and 124 controls).Results: cg06588802 ( LINC00299/ID2 ) showed a higher methylation in TNBC patients compared with controls (discovery set: 3% increase, p-value = 0.0009; validation set: 2% increase, p-value = 0.01). Consistent results at four neighboring methylation probes and the strong negative correlation (rho = -0.93) with LINC00299 expression add plausibility to this result.Conclusion: Hypermethylation of LINC00299 in peripheral blood may constitute a useful circulating biomarker for TNBC.